Bhutan - Public Financial Management Accountability Assessment - World Bank (World Bank, 2012)
This summary assessment uses indicator-led analysis to provide an integrated assessment of the Public Financial Management (PFM) system which draws on international standards developed by various development partners. The purpose is to measure PFM performance across a wide range of development over time. The Public Expenditure and Financial Accountability (PEFA) methodology includes the best conditions that some Organization for Economic cooperation and Development (OECD) countries demonstrate and in this assessment it is important to consider the Bhutanese context, that it is a small country, traditionally with an agricultural base society with relatively lesser industry and commerce. It is unable to support a financial sector infrastructure in terms of accountancy and audit standard setting and the availability of international standards is of great assistance. The 31 indicators for the PFM system focus on the basic qualities of a PFM system operating to existing good international practices, and assessments are classified A (excellent), B (good), C (opportunities for some improvement) and D (in need of substantial improvement in some areas or information not available for the assessment). Each indicator may have 1-4 dimensions each of which is assessed independently. The overall score for the indicator is based on the scores for the constituent dimensions in accordance with scoring rules established in the PEFA PFM framework document. In some circumstances a plus sign is added where the indicator takes on the score of the lowest scoring dimension but other dimensions have higher scores.